Tumor necrosis factors‐α inhibition‐induced paradoxical psoriasis: A case series and literature review. Issue 6 (15th September 2020) - Lian, Ni; Zhang, Li; Chen, Min
Abstract: Today, anti‐12/IL23, anti‐IL17, and anti‐IL23 provide more efficacious and/or safer treatment options for psoriasis. Though, anti‐TNF remains a gold standard in the therapy of chronic inflammatory diseases. Paradoxical psoriasis has been reported to occur in patients treated with TNF‐α inhibitors. According to the existing literature, including case reports, most patients with paradoxical psoriasis chose to stop the treatment immediately. This article presents a case series involving 150 patients with psoriasis who received treatments with TNF‐α inhibitors. We observed 10 (6.7%) patients developing paradoxical psoriasis, and they rejected the recommendation of immediate discontinuation and decided to continue the original treatment. Surprisingly, 80% of them achieved remission again after the aggravation of symptoms and did not have any other serious adverse event. However, there is currently little research that has clarified the mechanism of paradoxical psoriasis. Therefore, we also presented a review of the literature to determine the pathogenesis of paradoxical psoriasis and speculated on the possible causes of the observed transient exacerbation cases. Investigation of the pathogenesis of this paradoxical adverse reaction not only is helpful to guide clinicians to better manage patients, but also may contribute to the discovery of new therapeutic targets in the future.